DIGITAL LITERACY IN THEMATIC LEARNING OF ELEMENTARY SCHOOL STUDENTS WITH THE ASSISTANCE OF FLIPBOOK MEDIA - Dwi Yani; Ahmad Saifullah; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (Jurnal Konseling Pendidikan Islam, 2023)
This study aims to analyze digital literacy in thematic learning of elementary school students with the help of Flipbook media. To obtain data about digital literacy of elementary school students using questionnaires, observation sheets and in-depth interviews. Questionnaires were given to 23 grade VI elementary school students at SDN Trawas 1 who had operated flipbook media. For the validity and validity of the data conducted intensive interviews with students. Data analysis by reducing data in questionnaire tables, observation sheets and interviews. Then present it in narrative form to draw conclusions. The results of this study indicate that students' digital literacy in Thematic learning with the help of flipbook media is in the high category. Therefore thematic learning assisted by flipbook media needs to be developed and implemented so that elementary school students' digital literacy increases.